THE MODERN ANTI-FLU VACCINE IN THE NATIONAL IMMUNIZATION SCHEDULE FOR CHILDREN - A.V. Nekrasov; N.G. Puchkova (Union of pediatricians of Russia, 2009)
Grippol plus (LSR-006981/08-010908) is an influenza vaccine that will be applied in Russia in season 2009/2010 for children populations in the frames of National Immunization Schedule and «Zdorovie» Program. Influenza trivalent inactivated polymer-subunit vaccine is free from the preservative and is manufactured in comfortable package pre-filled ready-to-use syringes. The preparation is manufactured on the new production site in accordance with international quality standards (GMP). Immunological efficacy indexes for all three vaccine influenza virus strains comply with all three CPMP requirements for modern influenza vaccines. Vaccine is well tolerated by vaccineers and is low reactogenic. The results of clinical-epidemiological observations conducted in the season 2008-2009 with children of 3-17 years old show high vaccine efficacy and safety. Vaccine is recommended by specialists for children population annual immunoprophylaxis.Key words: influenza, vaccination, children.